Mycelial Menace: A Fusarium Horror in the Haematologic Shadows - Shing Yieng, Chew; Norashikin, Samsudin; Athirah, Mohammad; Nurnabilah, Zainuddin; Alisa Hanum, Arba’eni @ Arbaen (2025)
Acute myeloid leukaemia is one of the primary underlying conditions associated with invasive fusariosis, which often manifests as disseminated disease with pneumonia, fungaemia, and multiple skin lesions 1 . While yeast infections remain the predominant cause of fungaemia in patients with malignancies, the incidence of mould infections is rising and warrants greater clinical attention.